Pertumbuhan dan Hasil Tanaman Jagung Manis (Zea mays saccharata Sturt.) Dengan Pemberian Pupuk Organik Cair Daun Lamtoro dan Pupuk NPK - Solin, Nida Wafiqah Nabila M; Tobing, Arya Revanza; Taslapratama, Irwan (Agropross : National Conference Proceedings of Agriculture, 2023)
The use of organic fertilizers such as lamtoro leaf liquid organic fertilizer can be used to reduce the use of inorganic fertilizers in sweet corn cultivation. This study aims to obtain the concentration of lamtoro leaf liquid organic fertilizer and the efficient dose of NPK fertilizer for the growth and yield of sweet corn plants. The research was carried out at the UARDS Laboratory, Faculty of Agriculture and Animal Husbandry, UIN Sultan Syarif Kasim Riau. The study used a randomized block design (RBD) with 2 factors, namely the concentration of lamtoro leaf liquid organic fertilizer (0%, 30% and 50%) and the dose of NPK fertilizer (0 kg/ha, 200 kg/ha and 300 kg/ha). The results showed that treatment with a concentration of 30% POC in lamtoro leaves was efficient in increasing plant height, number of leaves and stem diameter. Treatment with a dose of 200 kg/ha of NPK fertilizer was efficient in increasing the number of leaves, stem diameter, cob length and cob weight without cob. There was no interaction between the POC treatment of lamtoro leaves and NPK fertilizer for all observed parameters in sweet corn plants.